Research trends in proton exchange membrane fuel cells during 2008–2018: A bibliometric analysis - Yonoff, Rony Escobar; Ochoa, Guillermo Valencia; Cardenas-Escorcia, Yulineth; Silva-Ortega, Jorge Iván; Meriño-Stand, Lourdes (Heliyon, 2019)
A bibliometric analysis of proton exchange membrane fuel cells (PEMFCs) content from a total of 15.020 research publications was conducted between 2008 and 2018, the papers being detailed in the online version of SCI-Expanded, Thomson Reuters Web of Science. Data processing tools such as Hitscite, CiteSpace, ArcGIS and Ucinet 6 were used to process the information. The parameters analyzed in the analysis were: type of document; the language of publication; volume and characteristics of publication output; publication by journals; performance of countries and research institutions; research trends and visibility. The study showed that "Fuel'', "Cell", "Membrane “and "Proton" were found in most of the titles of the documents, while "Performance", "Pemfc”, "Pem Fuel Cell" and "Fuel Cell" were the keywords most commonly used in documents. The analysis found that PEMFC studies have tended to be growing and that leading peer-reviewed journals have produced numerous publications on the subject. The investigation revealed that the country with the most significant production in the field is USA with a contribution of 3009; 20% of the total publications. Followed by China 2480; 16.5%, South Korea 1273; 8.5% and Germany 1121; 7.5%, showing to the main world powers as the most significant contributors to the research.